Thiolate-assisted route for constructing chalcogen quantum dots with photoinduced fluorescence enhancement - Zhang, Xiaodong (2022)
Despite great efforts in the development of diverse nanomaterials, a general route to synthesize metal-free chalcogen quantum dots (QDs) is still lacking. Moreover, the modification of chalcogen QDs is a bottleneck that severely hinders their applications. Herein, we develop a facile method to construct different chalcogen QDs (including S QDs, Se QDs, and Te QDs) with the assistance of thiolates. In addition to stabilizing chalcogen QDs, the thiolates also endow the chalcogen QDs with favorable modifiability. Different from most dyes whose fluorescence is quenched after short-term light irradiation, the prepared chalcogen QDs have significantly enhanced fluorescence emission under continuous light irradiation. Taking advantage of the distinctive photoinduced fluorescence enhancement property, long-time cell imaging with superb performance is realized using the chalcogen QDs. It is envisioned that the chalcogen QDs show promising potential as fluorescent materials in different fields beyond bioimaging.